2010
DOI: 10.1159/000314214
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and Vinorelbine as an All-Oral Chemotherapy in HER2-Negative Locally Advanced and Metastatic Breast Cancer

Abstract: Background: The oral formulation of vinorelbine together with capecitabine allows for an all-oral combination chemotherapy which promises to raise quality of life of patients with advanced breast cancer. Patients and Methods: Patients with HER2-negative, locally advanced, inoperable or metastatic breast cancer were included in this prospective observational trial (treatment schedule: capecitabine 500 mg/m2 twice daily, days 1–14; vinorelbine 60 mg/m2, days 1+8; repeated in 3-week cycles).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Interestingly, we obtained similar results to those achieved with standard regimens administered to metastatic breast cancer patients but avoiding toxicity. Accordingly, the use of gemcitabine and carboplatin plus iniparib yielded a 56% OCB rate [25], while the administration of capecitabine and vinorelbine in HER2-negative patients reached a OCB rate of 70% [26] and the combination of paclitaxel with gemcitabine resulted in a 80% OCB rate [27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we obtained similar results to those achieved with standard regimens administered to metastatic breast cancer patients but avoiding toxicity. Accordingly, the use of gemcitabine and carboplatin plus iniparib yielded a 56% OCB rate [25], while the administration of capecitabine and vinorelbine in HER2-negative patients reached a OCB rate of 70% [26] and the combination of paclitaxel with gemcitabine resulted in a 80% OCB rate [27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kandasamy, Chaturvedi et al [ 31 ] suggested that spiritual well-being is an important component of health promotion and coping with the illness of cancer patients and is closely related to the physical and psychological symptoms of distress and they added that it should be addressed appropriately and adequately in a palliative setting.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education and counseling can help reduce stress, improve coping skills, and can contribute to an improvement of the patients' health, which remains a high priority, especially in patients with metastatic disease. Inadequate health literacy, nonadherence, noncompliance, and other barriers present challenges to providing effective patient education [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common toxicities were hematological, including 12.9% of grade 3 neutropenia and 12.9% of grade 4 neutropenia; 9.7% of the patients had hand-foot syndrome. In May 2010, Gampenrieder et al [21 ]presented the results of a study associating capecitabine and oral vinorelbine (treatment schedule: capecitabine 500 mg/m 2 twice daily, days 1–14; vinorelbine 60 mg/m 2 , days 1 + 8; repeated in 3-week cycles). An overall clinical benefit rate of 70% was obtained.…”
Section: Discussionmentioning
confidence: 99%